INVESTIGATING THE USE OF MAXIMS IN THE EFL CLASS PRESENTATION: A PRAGMATIC STUDY - Febriana Aminatul Khusna; Sekar Lathifatul Aliyah; Dinar Ayu Asyifah (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
Maxim is one of the aspects studied in pragmatics, a relatively new field in linguistics. It is used in social interactions, especially in the form of conversations. In this study, the researchers conducted maxim analysis in an EFL class. The research data were collected from the WhatsApp-group communication of an online class in the English language education department of a public university in Central Java. This study employed a qualitative descriptive design using pragmatic analysis as its framework. There are maxim of quantity, maxim of quality, maxim of manner and maxim of relevance. The result shows that there were 22 occurrences of maxim of quantity with 5 cases of flouting of the maxim. Then, 28 occurrences belonged to maxim of quality and the researchers did not find any flouting of the maxim. Next, 26 occurrences were labelled as maxim of relevance with 2 cases of flouting of the maxim. Besides that, 22 occurrences were categorized as maxim of manner with 3 cases of flouting of the maxim. In general, 110 maxim occurrences were identified from 16 conversations recorded in this research.